Application Of Microseismic Monitoring In Underground Block Caving Mine - Septian Prahastudhi; Achmad Muttaqi; Eric Sitorus; Erwin Riyanto; Farid Gumilang (Institut Teknologi Sepuluh Nopember, 2018)
Induced mine activities could make impact to the rock’s stability. Block cave mine has some area where development of the progressing cave line and heading are disturbing and having risk to harm people working in the surrounding area. Rock mass in massive solid rock generates movement in order acting the stress that applied in the environment. Local movement in the mine where it’s caused by blasting – artificial source or passively occurs when the rock finds its stability is generating acoustic P and S waves. Microseismic monitoring system has been applied in the active mine area to ensure a safety production. This paper describes an application of real time microseismic monitoring system in underground mine operation to support a safety production.